Kompetenční profil státního úředníka - Rýznar, Ladislav (Univerzita Pardubice, 1999)
In Czech Republic was on Faculty of economics and administration realised expertise of requistition on state administration in 1998-1999. Characterisation within the framework of realised experties were formulated like postulates in four levels: qualifying, personalising, competenting and special. Closes experties supports, that necessary are for clerical workes of different authority of states administration agreeing.
Keywords: zaměstnanci; kvalifikace; požadavky; dovednosti; veřejná správa